INSPIRATIO: PAINTING BY ANDRIY ANTONYUK «TARAS SHEVCHENKO (IN THE CASEMATE)». INTERTEXTUALITY - Тарасенко, Андрій Андрійович; Тарасенко, Ольга Андріївна; Сікорська, Вікторія Юріївна (Art and Design, 2024)
The aim of the article is to study the image of poet-artist Shevchenko in the painting «Taras Shevchenko (in the casemate)» (1983) by prominent Ukrainian artist of folklore trend Andriy Antonyuk in the context of the theme «Inspiration» of world art. Historic-cultural-culturalogical, comparative, iconographic, iconologic, hermeneutic methods are used. Antoniuk shifted attention from the social aspect (inherent in the image of Shevchenko in the art of 1918-1938) to the spiritual level, expressing the idea of inspiration of the poet-prophet – a mediator between the world of earth and heaven. The harmony of word and image in the symbolic figurative structure of the picture-portrait of the artist-poet Shevchenko is revealed. Typological series of the iconography of Antoniuk’s composition are created. The scientific novelty of the publication lies in the fact that the image of Shevchenko in Antoniuk’s painting is investigated in the context of the theme of inspiration of the images of the world’s saints in art. It is shown that similar to the figures of fine art of the late XVIII – first half of XIX centuries Antoniuk interprets the iconography, traditional for the artistic embodiment of evangelists and enlightened figures of the church to depict a new hero: poet – artist – musician. It is presented that the expression of Shevchenko’s image is connected with the use of stylistics of Ukrainian folk art, Italian primitivism proto-Renaissance, art of leftist trends of the early twentieth century (expressionism, neoprimitivism). Practical significance. The presented materials, their artistic and stylistic analysis and generalization can be used in scientific studies on the art of Shevchenko’s portrait.